A clear signature of the breakup modes for 9Be on a proton target at 5.6 MeV/nucleon. (December 2020) - Pakou, A; Sgouros, O; Soukeras, V; Cappuzzello, F; Acosta, L; Agodi, C; Boiano, A; Calabrese, S; Carbone, D; Cavallaro, M; Deshmukh, N N; Foti, A; et al.
Abstract: The breakup of 9 Be is studied via an inelastic scattering experiment on a proton target at 5.6 A MeV in inverse kinematics. Two of the three cluster constituents ( α and α ) as well as the proton target recoil were recorded in a triple coincidence mode allowing a full kinematics approach analysis. In this respect relative α - α and α - n, Q-value and 9 Be excitation spectra, energy spectra for all fragments as well as the energy spectrum of the recoil proton were reconstructed. A clear signature of the two breakup sequential modes ( 5 He + 4 He and 8 Be + n) was identified via the recoiling proton reconstructed spectra together with the direct breakup decay. A strong 5 He + 4 He mode was observed compatible with previous beta decay experiments.